CGIAR Research Initiative Proposal Review Report: Accelerating Crop Improvement through Genome Editing - CGIAR Independent Science for Development Council (CGIAR Independent Science for Development Council, 2022)
Prepared for the 16th meeting of System Council held on July 20, 2022, this report proposes an external review of the “Accelerating Crop Improvement through Genome Editing” CGIAR Initiative proposal. The external review of Initiative proposals is an essential part of good governance and quality assurance, delivering benefits for the researchers, leadership, and System Council. The review presented in this report provide confidence to funders that their investments in One CGIAR research are appropriately targeted with high chances for success. The Initiative reviews occurred in several waves and subsequently the reporting are presented by waves. The first wave report (19 Initiative proposals) was published for the 14th Meeting of the System Council in November 2021 and the second wave (12 Initiative proposals) for the 15th Meeting of the System Council in March 2022.